Development of the CBT-E Components Checklist: A tool for measuring therapist self-rated adherence to CBT-E - Bailey-Straebler, S; Cooper, Z; Dalle Grave, R; Calugi, S; Murphy, R (Positive Press, 2022)
Few tools to encourage therapists to implement evidence based psychological treatments as designed exist. Assessing therapist “competence” (implementing therapeutic procedures well) by evaluating the quality of their treatment sessions is problematic for multiple reasons. Therapist self-rated measures of “adherence” (using the correct therapeutic procedures) may offer a viable alternative. We describe (i) the development of a CBT-E Components Checklist (CBT-E CC) for therapists, as well as (ii) how to use the CBT-E CC and where to access it. The CBT-E CC is an adherence checklist for enhanced cognitive behavior therapy for eating disorders (CBT-E). It is intended as a formative tool for therapists to assess, and improve as needed, their own adherence. Future research on the validity of the checklist to accurately measure adherence is needed.